Effect of acidification on starter pig performance and nutrient digestibility - Weeden, T.L.; Hansen, J.A.; Richardson, K.L.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred ninety-six pigs (21 d of age and 12.3 lb initial wt) were used to evaluate the effect of adding an organic acid blend (OAB) to starter diets on growth performance and nutrient digestibility. The four dietary treatments consisted of a control diet and the GAB replacing corn at 3, 4.5, and 6 lb/ton in both phases 1 and 2. In phase 1 (0 to 14 d) diets, contained 20% dried skim milk, 20% dried whey, and 5% soybean oil. Phase 2 diets (15 to 35 d) contained 10% dried whey and 5% soybean oil. There was no response in ADG, FI, or F/G to the addition of OAB to starter diets in either phase 1 or phase 2. Fecal samples were collected on d 12 (phase 1) of the experiment via rectal massage, and apparent digestibility of nitrogen and dry matter were calculated using chromic oxide (.25%) as an indigestible marker. Nitrogen and dry matter digestibility decreased linearly with increasing levels of OAB. This trial demonstrates that addition of OAB has no effect on performance when pigs consumed high milk-product diets.
Keywords: Swine; Starter; Performance; Digestion; Acid